2021
DOI: 10.1101/2021.05.17.444514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cre-dependent massively parallel reporter assay allows for cell-type specific assessment of the functional effects of non-coding elementsin vivo

Abstract: Human genetic studies have identified a large number of disease-associated de novo variants in presumptive regulatory regions of the genome that pose a challenge for interpretation of their effects: the impact of regulatory variants is highly dependent on the cellular context, and thus for psychiatric diseases these would ideally be studied in neurons in a living brain. Furthermore, for both common and rare variants, it is expected that only a subset fraction will affect gene expression. Massively Parallel Rep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
4
0
1
Order By: Relevance
“…Our results in cell lines indicated that a subset of 5′UTR mutations from patients can alter protein production of host genes. However, regulation of translation can be cell type-specific (Cottrell et al, 2018; Lagunas et al, 2023), as certain factors such as the expression of helicases, initiation factors, and other RNA-binding proteins can vary between cellular contexts. Developing neurons are likely the most important cell type for autism (Fu et al, 2022; Li et al, 2023; Satterstrom et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results in cell lines indicated that a subset of 5′UTR mutations from patients can alter protein production of host genes. However, regulation of translation can be cell type-specific (Cottrell et al, 2018; Lagunas et al, 2023), as certain factors such as the expression of helicases, initiation factors, and other RNA-binding proteins can vary between cellular contexts. Developing neurons are likely the most important cell type for autism (Fu et al, 2022; Li et al, 2023; Satterstrom et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Developing neurons are likely the most important cell type for autism (Fu et al, 2022; Li et al, 2023; Satterstrom et al, 2020). Therefore, we have previously adapted an MPRA for cell type-specific measures in neurons in vivo (Lagunas et al, 2023). Our previous approach was not sensitive enough to detect the effect of variants due to technical limitations of measuring small effect sizes with relatively few barcodes per reporter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Соматические мутации в 5'-нетранслируемых областях генов, которые потенциально влияют на эффективность трансляции, также обнаруживаются в клетках рака [164,165]. Использование МПРА позволило идентифицировать мутации в некодирую щих областях генов, ассоциированные с раком простаты [166], болезнями аутистического спект ра [167], а также с другими патологическими состоя ниями и признаками человека [98,168].…”
Section: применение массового параллельного репортерного анализа для ...unclassified
“…Likewise, loss-of-function enhancer variants often result in loss of enhancer activity in one cell type, while in other cell types, its activity is unaffected (Bengani et al, 2021; Bhatia et al, 2015, 2021; Shin et al, 2023; Spieler et al, 2014). These cell-type-specific effects of enhancer variants are difficult to capture with high-throughput methods such as massively-parallel reporter assays (MPRAs) and CRISPR inhibitor/activator screens, both of which are primarily performed in vitro (Findlay, 2021; Inoue & Ahituv, 2015; Maricque et al, 2018) or in one tissue (Brown et al, 2022; Capauto et al, 2023; Deng et al, 2023; Lagunas et al, 2023; Patwardhan et al, 2012; White et al, 2013). Transgenic enhancer-reporter assays in mice enable visualization of enhancer activity in the whole animal and are a gold-standard for functionally testing when and where a human enhancer is active in vivo (Kothary et al, 1989; Pennacchio et al, 2006; Visel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%